2001
DOI: 10.1203/00006450-200111000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Liganded and Unliganded Steroid Receptor Modulation of Beta 1 Adrenergic Receptor Gene Transcription

Abstract: The classical model of gene regulation by hormones involves a hormone-bound receptor interacting with a DNA response element to increase or decrease gene transcription. Steroid hormone regulation more commonly involves atypical cis-elements, co-receptors, accessory proteins, and unique modes of interaction on different genes. The thyroid hormone and retinoic acid receptors belong to the super family of steroid nuclear receptors and may modify gene expression even in the absence of ligand binding. In these stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 52 publications
(90 reference statements)
1
0
0
Order By: Relevance
“…Major transcriptional regulators of β-AR genes include glucocorticoid- and thyroid hormone-responsive elements (GREs and TREs, respectively), with glucocorticoids downregulating β1-ARs and upregulating β2-ARs29. Thyroid hormone can upregulate β1-AR gene transcriptional activity30 whereas chronic exposure to β-AR-agonist results in downregulation of β1-AR protein and mRNA31. In the present study, we observed an increase in β2-AR/G i proteins in CaMKIIδ KO mice.…”
Section: Resultssupporting
confidence: 52%
“…Major transcriptional regulators of β-AR genes include glucocorticoid- and thyroid hormone-responsive elements (GREs and TREs, respectively), with glucocorticoids downregulating β1-ARs and upregulating β2-ARs29. Thyroid hormone can upregulate β1-AR gene transcriptional activity30 whereas chronic exposure to β-AR-agonist results in downregulation of β1-AR protein and mRNA31. In the present study, we observed an increase in β2-AR/G i proteins in CaMKIIδ KO mice.…”
Section: Resultssupporting
confidence: 52%